Konsep Doa Yesus Kristus menurut Yohanes 17:1-26 - Bertha Tarigan (STT Injili Indonesia Medan, 2019)
The life of Jesus in the New Testament had been model for christianity, especially His prayer. The right prayer concept is like Jesus’s prayer in John 17: 1-26, where He prayed for Himself, His Disciples and others. It’s concept must be the basis of Christian prayer. This article will explain the exposition of the concept of Jesus’s prayer in accordance with the Gospel of John 17: 1-26.